Intumescent resin anchoring agent

By using the expansion resin anchoring agent, the expansion is used to generate carbon dioxide gas to improve the bonding strength, which solves the problem of high -strength bonding under the condition of complex crushing soft rocks in existing technologies, and achieves effective support for the mineral body.

CN119349928APending Publication Date: 2025-01-24TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411472251.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing organic resin anchoring agent is difficult to bond with the surrounding rock mass under complex crushed soft rock conditions, resulting in difficulty in supporting.

Method used

Intumescent resin anchoring agent is used, which is composed of intumescent resin cement and intumescent curing agent, including unsaturated polyester resin, stone powder, thixotropic agent, accelerator and expanding agent. Through expansion, carbon dioxide gas is generated to improve adhesion. strength.

Benefits of technology

Under the conditions of complex crushing soft rocks, the expansion resin anchor agent can fill the crack rock body and perform high -intensity bonding with the mineral body to achieve effective support for the ore body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349928A_ABST
    Figure CN119349928A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anchoring agents, and discloses an intumescent resin anchoring agent. The invention relates to an intumescent resin anchoring agent which is formed by compounding intumescent resin mortar and an intumescent curing agent according to the mass ratio of (4-8): 100. Wherein the expansive resin mortar is prepared from the following raw materials in parts by mass: 150 to 250 parts of unsaturated polyester resin, 730 to 830 parts of stone powder, 18 to 23 parts of thixotropic agent, 2 to 4 parts of accelerant and 3 to 10 parts of expanding agent A; and the intumescent curing agent comprises the following raw materials in parts by mass: 90-190 parts of a curing agent and 3-18 parts of an expanding agent B. The expansive type resin anchoring agent disclosed by the invention has excellent expansive performance and bonding strength, can be used for filling fractured rock masses and can be bonded with ore bodies under the condition of complex broken soft rocks, and effective supporting of the ore bodies is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anchoring agents, in particular to an expansion type resin anchoring agent. Background Art

[0002] Anchoring agents serve as a bonding agent between anchor rods and loose surrounding rock masses. Relying on the interaction among anchor rods, loose surrounding rock masses and anchoring agents, the loose surrounding rock masses are reinforced, allowing subsequent production and life work to proceed. Organic resin anchoring agents generally use unsaturated polyester resins, which have the advantages of good bonding properties, high fluidity, high strength after curing, good thermal stability, and good mechanical stability. Therefore, organic resin anchoring agents have broad application prospects. However, when faced with complex broken soft rock conditions such as plastic zone malignant expansion areas, fault fracture zones, and water-containing soft rocks, organic resin anchoring agents are difficult to bond with the surrounding rock masses with high strength, resulting in support difficulties and other problems. Therefore, the preparation of an anchoring agent that can bond with the surrounding rock masses with high strength under complex broken soft rock conditions has become a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0003] The purpose of the present invention is to provide an expandable resin anchoring agent, which can fill the fractured rock mass under the condition of complex broken soft rock and can bond with the ore body with high strength, thereby realizing effective support for the ore body.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] One of the technical solutions of the present invention:

[0006] An expandable resin anchoring agent is compounded by an expandable resin cement and an expandable curing agent in a mass ratio of (4-8):100.

[0007] Furthermore, the expandable resin mortar comprises the following raw materials in parts by weight: 150-250 parts of unsaturated polyester resin, 730-830 parts of stone powder, 18-23 parts of thixotropic agent, 2-4 parts of accelerator and 3-10 parts of expander A.

[0008] Furthermore, the unsaturated polyester resin is MG196 type o-phthalic unsaturated polyester resin or an unsaturated polyester resin with similar properties.

[0009] The present invention adds unsaturated polyester resin to the expandable resin mortar, which can effectively improve the support performance of the anchoring agent; firstly, as a high-performance polymer material, the unsaturated polyester resin has excellent mechanical properties, which enables the anchoring agent to have higher compressive strength and higher tensile strength, thereby effectively improving the support performance of the anchoring agent; secondly, the unsaturated polyester resin has excellent heat resistance and corrosion resistance, which enables the anchoring agent to still maintain excellent support performance under harsh conditions such as high temperature and corrosion; in addition, the unsaturated polyester resin also has excellent bonding properties, and shows good bonding properties to both metal and non-metal materials, and can also improve the support performance of the anchoring agent to a certain extent.

[0010] Furthermore, the stone powder is one or more of dolomite powder, limestone powder, porcelain powder and calcium carbonate powder.

[0011] The present invention adds stone powder to the expansion resin mortar, which can effectively improve the compressive strength of the anchoring agent;

[0012] The present invention has found that there is no significant difference in the ability of different types of stone powder to improve the compressive strength of the anchor. Therefore, the type of stone powder can be reasonably selected based on economic benefits; and different stone powder particle sizes can enhance the compressive strength of the anchor to a certain extent; specifically, limestone powder with particle sizes of 10 mesh to 20 mesh, 20 mesh to 80 mesh, and 80 mesh to 100 mesh mixed in a mass ratio of 1:2:1 can most effectively improve the compressive strength of the anchor.

[0013] Furthermore, the thixotropic agent is white carbon black.

[0014] The invention adds white carbon black thixotropic agent to the swelling resin mortar, which can ensure that the unsaturated polyester resin and the stone powder will not have the problems of stratification and penetration after being mixed, so as to ensure the successful preparation of the anchoring agent.

[0015] Furthermore, the accelerator is one or more of N,N-dimethylaniline (DMA) and N,N-dimethyl-p-toluidine (DMT);

[0016] The present invention adds an accelerator to the swelling resin mortar, which can promote the gelation of the anchoring agent and realize the solidification of the anchoring agent;

[0017] The present invention has found that when the type and amount of the accelerator are different, different curing speeds of the anchoring agent can be achieved; specifically, when N,N-dimethylaniline and N,N-dimethyl-p-toluidine are mixed and added at a mass ratio of 1:2, it can achieve ultra-fast curing of the anchoring agent; while when only N,N-dimethylaniline is used as the accelerator, it can only achieve relatively fast curing of the anchoring agent.

[0018] Furthermore, the expansion agent A is one or more of aluminum sulfate, aluminum nitrate, ferric sulfate and ferric nitrate.

[0019] Furthermore, the intumescent curing agent comprises the following raw materials in parts by mass: 90 to 190 parts of curing agent and 3 to 19 parts of intumescent agent B.

[0020] The intumescent curing agent of the present invention has the function of rapidly curing the intumescent resin cement, so that the intumescent resin cement has good chemical corrosion resistance, moisture resistance and temperature resistance, and can maintain stable performance under harsh environmental conditions;

[0021] According to the curing speed, curing agents can be divided into medium-speed expansion curing agents, fast expansion curing agents, and super-fast expansion curing agents.

[0022] Furthermore, the expansion agent B is sodium bicarbonate.

[0023] The expansion effect of the resin anchoring agent of the present invention is produced by selecting a strong acid salt that does not react with other raw materials in the expandable resin cement as the expansion agent A and selecting sodium bicarbonate that does not react with other raw materials in the expandable curing agent as the expansion agent B, stirring and mixing them in a solution state to quickly generate carbon dioxide gas.

[0024] The second technical solution of the present invention:

[0025] The preparation method of the above-mentioned expandable resin anchoring agent comprises the following steps:

[0026] Weigh the raw materials according to the mass parts, mix the unsaturated polyester resin, stone powder, thixotropic agent, accelerator and expansion agent A to obtain the expandable resin putty; mix the curing agent and the expansion agent B to obtain the expandable curing agent; and pack the expandable resin putty and the expandable curing agent into two independent chambers of the mother-child bag to obtain the expandable resin anchoring agent.

[0027] The third technical solution of the present invention:

[0028] The application of the above-mentioned expandable resin anchoring agent in ore body support comprises the following steps:

[0029] Anchor the expandable resin anchor into the matrix that needs support.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The expandable resin anchor prepared by the present invention has excellent expansion performance and excellent bonding strength. Therefore, the expandable resin anchor prepared by the present invention can fill the fractured rock mass under complex broken soft rock conditions and can be bonded with the ore body with high strength, thereby achieving effective support for the ore body. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0033] Figure 1 This is a graph showing the changing trend of expansion rate of different anchoring agents as the amount of expansion agent increases;

[0034] Figure 2 This is a graph showing the changing trend of gel time of different anchoring agents as the amount of expansion agent increases;

[0035] Figure 3 This is a graph showing the changing trend of compressive strength of different anchoring agents as the amount of expansion agent increases;

[0036] Figure 4 This is a graph showing the changing trend of anchoring force of different anchoring agents as the amount of expansion agent increases; DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the following examples, unless otherwise specified, "parts" are parts by mass, and are weighed according to 1 part = 1 g.

[0039] In the following embodiments, the expandable resin anchoring agent is compounded by an expandable resin mastic and an expandable curing agent in a mass ratio of (4-8):100.

[0040] The expandable resin mortar includes the following raw materials by weight: 150-250 parts of unsaturated polyester resin, 730-830 parts of stone powder, 18-23 parts of thixotropic agent, 2-4 parts of accelerator and 3-10 parts of expander A;

[0041] The unsaturated polyester resin is MG196 type o-phthalic unsaturated polyester resin or an unsaturated polyester resin with similar properties;

[0042] The stone powder is one or more of dolomite powder, limestone powder, porcelain powder and calcium carbonate powder;

[0043] In the following embodiments, limestone powder is used as raw material because research has found that different types of stone powder have no significant difference in their ability to improve the compressive strength of the anchoring agent, and limestone powder raw materials are widely available and inexpensive, which can achieve higher economic benefits;

[0044] The thixotropic agent is white carbon black;

[0045] The accelerator is one or more of N,N-dimethylaniline (DMA) and N,N-dimethyl-p-toluidine (DMT);

[0046] The expansion agent A is one or more of aluminum sulfate, aluminum nitrate, ferric sulfate and ferric nitrate;

[0047] Aluminum sulfate is used as a raw material in the following examples because it is found that the expansion performance of the prepared anchoring agents using different expansion agents A as anchoring agent raw materials is not significantly different, so aluminum sulfate is used as an example in the examples;

[0048] The intumescent curing agent comprises the following raw materials in parts by weight: 90 to 190 parts of curing agent and 3 to 19 parts of expansion agent B;

[0049] According to the curing speed, curing agents can be divided into medium-speed expansion curing agents, fast expansion curing agents, and super-fast expansion curing agents;

[0050] The expansion agent B is sodium bicarbonate.

[0051] The raw materials described in the following examples are all commercially available, wherein the MG196 type o-phthalic unsaturated polyester resin is purchased from Huaibei Yuxin New Materials Co., Ltd.; the limestone powder is purchased from Shanxi Chengjiu Industry and Trade Co., Ltd.; the white carbon black is purchased from Zhuzhou Xinglong New Materials Co., Ltd.; the N,N-dimethylaniline is purchased from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.; the N,N-dimethyl-p-toluidine is purchased from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.; the aluminum sulfate is purchased from Tianjin Zhonghe Shengtai Chemical Co., Ltd.; the medium-speed curing agent is purchased from Huaibei Yuxin New Materials Co., Ltd.; the fast curing agent is purchased from Huaibei Yuxin New Materials Co., Ltd.; the ultra-fast curing agent is purchased from Huaibei Yuxin New Materials Co., Ltd.; the sodium bicarbonate is purchased from Weifang Haizhiyuan Chemical Co., Ltd.

[0052] Example 1

[0053] A super fast expansion resin anchoring agent

[0054] 1) Weigh 200 parts of MG196 type o-phthalic unsaturated polyester resin (unsaturated polyester resin), 800 parts of limestone powder (stone powder) with particle sizes of 10 mesh to 20 mesh, 20 mesh to 80 mesh and 80 mesh to 100 mesh in a mass ratio of 1:2:1, 20 parts of white carbon black (thixotropic agent), 1 part of N,N-dimethylaniline (accelerator), 2 parts of N,N-dimethyl-p-toluidine (accelerator) and 3 parts of aluminum sulfate (expanding agent A);

[0055] 2) mixing the raw materials weighed in step 1) and stirring for 60 minutes to obtain an intumescent resin cement;

[0056] 3) Weigh 140 parts of super fast curing agent and 3 parts of sodium bicarbonate (expansion agent B);

[0057] 4) mixing the raw materials weighed in step 3) and stirring for 60 minutes to obtain an intumescent curing agent;

[0058] 5) The intumescent resin cement obtained in step 2) and the intumescent curing agent obtained in step 4) are packed into two independent chambers of a mother-and-child bag at a mass ratio of 4.5:100 to obtain the ultra-fast intumescent resin anchoring agent.

[0059] In Example 1, the proportion of the expander is 2.1%.

[0060] Embodiments 2 to 6

[0061] A super fast expansion resin anchoring agent

[0062] The same as Example 1, except that: each raw material is weighed according to the mass parts recorded in Table 1;

[0063] Table 1 Raw material ratio (parts by mass)

[0064]

[0065] Example 7

[0066] A fast expansion resin anchoring agent

[0067] 1) Weigh 200 parts of MG196 type o-phthalic unsaturated polyester resin (unsaturated polyester resin), 800 parts of limestone powder (stone powder) with particle sizes of 10 mesh to 20 mesh, 20 mesh to 80 mesh and 80 mesh to 100 mesh in a mass ratio of 1:2:1, 20 parts of white carbon black (thixotropic agent), 3 parts of N,N-dimethylaniline (accelerator) and 3 parts of aluminum sulfate (expanding agent A);

[0068] 2) mixing the raw materials weighed in step 1) and stirring for 60 minutes to obtain an intumescent resin cement;

[0069] 3) Weigh 140 parts of fast curing agent and 3 parts of sodium bicarbonate (expansion agent B);

[0070] 4) mixing the raw materials weighed in step 3) and stirring for 60 minutes to obtain an intumescent curing agent;

[0071] 5) The intumescent resin cement obtained in step 2) and the intumescent curing agent obtained in step 4) are packed into two independent chambers of a mother-and-child bag at a mass ratio of 4.5:100 to obtain the rapid intumescent resin anchoring agent.

[0072] In Example 7, the proportion of the expander is 2.1%.

[0073] Embodiments 8 to 12

[0074] A fast expansion resin anchoring agent

[0075] Same as Example 7, except that: each raw material is weighed according to the mass parts recorded in Table 2;

[0076] Table 2 Raw material ratio (parts by mass)

[0077]

[0078] Example 13

[0079] A medium-speed expansion resin anchoring agent

[0080] 1) Weigh 200 parts of MG196 type o-phthalic unsaturated polyester resin (unsaturated polyester resin), 800 parts of limestone powder (stone powder) with particle sizes of 10 mesh to 20 mesh, 20 mesh to 80 mesh and 80 mesh to 100 mesh in a mass ratio of 1:2:1, 20 parts of white carbon black (thixotropic agent), 3 parts of N,N-dimethylaniline (accelerator) and 3 parts of aluminum sulfate (expanding agent A);

[0081] 2) mixing the raw materials weighed in step 1) and stirring for 60 minutes to obtain an intumescent resin cement;

[0082] 3) Weigh 3 parts of medium-speed curing agent and sodium bicarbonate (expansion agent B);

[0083] 4) mixing the raw materials weighed in step 3) and stirring for 60 minutes to obtain an intumescent curing agent;

[0084] 5) The intumescent resin cement obtained in step 2) and the intumescent curing agent obtained in step 4) are packed into two independent chambers of a mother-and-child bag at a mass ratio of 4.5:100 to obtain the medium-speed intumescent resin anchoring agent.

[0085] In Example 13, the proportion of the expander is 2.1%.

[0086] Embodiments 14 to 18

[0087] A medium-speed expansion resin anchoring agent

[0088] Same as Example 13, except that: each raw material is weighed according to the mass parts recorded in Table 3;

[0089] Table 3 Raw material ratio (parts by mass)

[0090]

[0091] Effect verification

[0092] 1. Free expansion rate test

[0093] The free expansion rate of the expandable resin anchoring agent prepared in Examples 1 to 18 was tested;

[0094] The free expansion rate test method is:

[0095] 1) Brush a layer of demoulding liquid on the inner wall of a 40mm×40mm×40mm mold, add the intumescent resin putty and intumescent curing agent into the mold, then use a metal rod to quickly stir, compact, demould, and measure the volume of the anchor block;

[0096] 2) After the expandable resin anchoring agent is completely cured, the volume of the anchoring block is measured and the free expansion rate is calculated according to the following formula. The experiment is repeated three times in parallel;

[0097]

[0098] The free expansion rate test results are as follows: Figure 1 As shown;

[0099] Depend on Figure 1 It can be seen that with the increase in the amount of expansion agent, the super-fast anchor, fast anchor and medium-speed anchor all have obvious expansion effects, which are basically positively correlated. The expansion rate can be controlled within the expansion rate of 0% to 25%.

[0100] 2. Gel time detection

[0101] The gel time of the expandable resin anchoring agents prepared in Examples 1 to 18 was tested;

[0102] The gel time detection method is:

[0103] 1) Place the intumescent resin putty and intumescent curing agent in the center of the polyester film and stir quickly and evenly;

[0104] 2) Record the temperature and time from the start of stirring. When the anchoring agent thickens and the temperature begins to rise, the recorded time is the gel time of the expandable resin anchoring agent. The experiment is repeated three times;

[0105] The gel time standards of different resin anchoring agents are shown in Table 4;

[0106] Table 4 Gel time standard of different resin anchoring agents

[0107]

[0108] Note: Measured at an ambient temperature of (22±1)℃;

[0109] The gel time test results are as follows Figure 2 As shown;

[0110] Depend on Figure 2 It can be seen that for the ultra-fast anchor, as the amount of the expansion agent increases, the gel time fluctuates in the range of 27 to 30 s, which meets the CKa type standard of 26 to 40 s; for the fast anchor, as the amount of the expansion agent increases, the gel time fluctuates in the range of 60 to 70 s, which meets the K type standard of 41 to 91 s; for the medium-speed anchor, as the amount of the expansion agent increases, the gel time fluctuates in the range of 120 to 140 s, which meets the Z type standard of 91 to 180 s; therefore, the expansive resin anchors prepared by the present invention all meet the gel time standards.

[0111] 3. Compressive strength test

[0112] The compressive strength of the expandable resin anchoring agents prepared in Examples 1 to 18 was tested;

[0113] The compressive strength test method is:

[0114] 1) Brush a layer of demoulding liquid on the inner wall of a 40mm×40mm×40mm mold, add the intumescent resin putty and intumescent curing agent into the mold, then use a metal rod to quickly stir, compact, and demould;

[0115] 2) After standing for 24 hours, use a pressure testing machine to perform a compression test and record the compressive load value;

[0116] The compressive strength test results are as follows Figure 3 As shown;

[0117] Depend on Figure 3 It can be seen that the compressive strength of ultra-fast anchors, fast anchors and medium-speed anchors decreases with the increase of expansion rate. However, within the expansion range of 0% to 20%, the compressive strength of various anchors is greater than the anchor compressive strength standard (60MPa). Therefore, the 0% to 20% expansion type resin anchor prepared by the present invention can meet actual industrial needs.

[0118] 4. Anchoring force detection

[0119] The anchoring force of the expandable resin anchoring agents prepared in Examples 1 to 18 was tested;

[0120] The anchoring force detection method is:

[0121] Place the anchor in the test steel pipe, then install the anchor rod to the drilling rig, rotate and stir while pushing, loosen the stirring connection device after the anchor gels, and conduct an anchoring force test after the anchor has reached a specified age;

[0122] The anchoring force test results are as follows: Figure 4 As shown;

[0123] Depend on Figure 4 It can be seen that within the expansion range of 0% to 20% of the anchor, the anchoring force of the super-fast anchor, the fast anchor and the medium-speed anchor all increase with the increase of the expansion rate; for the medium-speed anchor, the average anchoring force of the anchor with a 5% expansion rate is 172.3kN, and the average anchoring force increases by 12.8%; the average anchoring force of the anchor with a 10% expansion rate is 189.3kN, and the average anchoring force increases by 23.9%; the average anchoring force of the anchor with a 20% expansion rate is 205.7kN, and the average anchoring force increases by 34.7%; for the fast anchor, the average anchoring force of the anchor with a 5% expansion rate is 175kN, and the average anchoring force increases by 16.8%. The average value increased by 16.1%; the average anchoring force of the anchor with a 10% expansion rate was 187.3kN, and the average anchoring force increased by 24.3%; the average anchoring force of the anchor with a 20% expansion rate was 200.7kN, and the average anchoring force increased by 33.2%; for ultra-fast anchors, the average anchoring force of the anchor with a 5% expansion rate was 180.7kN, and the average anchoring force increased by 12.7%; the average anchoring force of the anchor with a 10% expansion rate was 201.7kN, and the average anchoring force increased by 25.8%; the average anchoring force of the anchor with a 20% expansion rate was 216.3kN, and the average anchoring force increased by 34.9%.

[0124] In summary, the expandable resin anchor prepared by the present invention has excellent expansion performance and excellent bonding strength. Therefore, the expandable resin anchor prepared by the present invention can fill the fractured rock mass under complex broken soft rock conditions and can bond with the ore body with high strength, thereby realizing effective support for the ore body.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. An expandable resin anchoring agent, characterized in that: The expandable resin anchoring agent is compounded by an expandable resin cement and an expandable curing agent in a mass ratio of (4-8):

100.

2. An expandable resin anchoring agent according to claim 1, characterized in that: The intumescent resin mortar comprises the following raw materials in parts by weight: 150-250 parts of unsaturated polyester resin, 730-830 parts of stone powder, 18-23 parts of thixotropic agent, 2-4 parts of accelerator and 3-10 parts of expansion agent A.

3. An expandable resin anchoring agent according to claim 2, characterized in that: The unsaturated polyester resin is MG196 type o-phthalic unsaturated polyester resin or an unsaturated polyester resin with similar performance; the stone powder is one or more of dolomite powder, limestone powder, porcelain powder and calcium carbonate powder.

4. An expandable resin anchoring agent according to claim 2, characterized in that: The thixotropic agent is white carbon black; the accelerator is one or more of N,N-dimethylaniline and N,N-dimethyl-p-toluidine.

5. An expandable resin anchoring agent according to claim 2, characterized in that: The expansion agent A is one or more of aluminum sulfate, aluminum nitrate, ferric sulfate and ferric nitrate.

6. An expandable resin anchoring agent according to claim 1, characterized in that: The intumescent curing agent comprises the following raw materials in parts by weight: 90 to 190 parts of curing agent and 3 to 18 parts of intumescent agent B.

7. An expandable resin anchoring agent according to claim 6, characterized in that: The expansion agent B is sodium bicarbonate.

8. A method for preparing the expandable resin anchoring agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh the raw materials according to the mass parts, mix the unsaturated polyester resin, stone powder, thixotropic agent, accelerator and expansion agent A to obtain the expandable resin putty; mix the curing agent and the expansion agent B to obtain the expandable curing agent; and pack the expandable resin putty and the expandable curing agent into two independent chambers of the mother-child bag to obtain the expandable resin anchoring agent.

9. An application of the expandable resin anchoring agent according to any one of claims 1 to 8 in ore support, characterized in that: The following steps are involved: Anchor the expandable resin anchor into the matrix that needs support.

Citation Information

Cited By

  • Intumescent resin anchoring agent and preparation method thereof

    CN121135221A